Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1074/jbc.ra119.012438
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase B from Corynebacterium diphtheriae catalyzes sulfoxide reduction via an intramolecular disulfide cascade

Abstract: Corynebacterium diphtheriae is a human pathogen that causes diphtheria. In response to immune system-induced oxidative stress, C. diphtheriae expresses antioxidant enzymes, among which are methionine sulfoxide reductase (Msr) enzymes, which are critical for bacterial survival in the face of oxidative stress. Although some aspects of the catalytic mechanism of the Msr enzymes have been reported, several details still await full elucidation. Here, we solved the solution structure of C. diphtheriae MsrB (Cd-MsrB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…Mass spectometry analysis was performed as described previously 54 , 55 . After immunoprecipitation, samples were resolved using a 10% Tris–Glycine SDS-PAGE and proteins were visualized using PageBlue (Thermo Scientific, 24,620).…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectometry analysis was performed as described previously 54 , 55 . After immunoprecipitation, samples were resolved using a 10% Tris–Glycine SDS-PAGE and proteins were visualized using PageBlue (Thermo Scientific, 24,620).…”
Section: Methodsmentioning
confidence: 99%
“…MsrB (I6YA00), Thiol peroxidase (Tpx, P9WG35 ), and Alkyl hydroperoxide reductase C (AhpC, P9WQB7 ) have been reported as the key elements in the defense against oxidative stress in Mtb ( 24 , 35 , 36 ). And the cysteine of Thiol peroxidase from Escherichia coli and MsrB from C. diphtheriae could be oxidized to sulfuric acid (SOH) by peroxide ( 37 , 38 ). Interestingly, elongation factors were reported as targets of oxidation by ROS via the oxidation of cysteine residues to SOH ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that residues within the CoAlated cysteine environment contribute to the stabilization of both CoA and the CoAlated cysteine, facilitating CoAlation. Similar to CoA, glutathione (GSH— Figure 4 A), mycothiol and bacillithiol are low molecular weight (LMW) thiols, which protect protein cysteines from hyperoxidation and are implicated in redox signaling [ 19 , 27 , 47 , 48 ]. Although research on the detailed site(s) of mycothiolation/bacillithiolation is not thoroughly discussed, protein glutathionylation on the other hand, is well studied [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…When sulfenic acid is formed on a cysteine, LMW thiols (GSH, BSH, MSH and CoA) can perform a nucleophilic attack on the sulfur atom of the sulfenic acid and form a mixed-disulfide bond in a process termed thiolation (glutathionylation, bacillithiolation, mycothiolation and CoAlation). This prevents the hyperoxidation of the protein cysteine and in many cases, its irreversible loss of function [ 8 , 10 , 18 , 19 , 20 , 21 ] ( Figure 1 B). Protein thiolation could also occur through thiol-disulfide exchange reactions.…”
Section: Introductionmentioning
confidence: 99%